Moderating Task Complexity in the Influence of Locus of Control, Self-Efficacy, and Time Budget Pressure on Audit Judgment: A Bibliometric Analysis - Erlangga Prakasa; Poppy Sofia Koeswayo; Ahmad Zakie Mubarrok (Universitas KH. Abdul Chalim Mojokerto, 2025)
Auditors play a crucial role in ensuring that the financial statements presented by audited entities are prepared fairly and accurately. In the auditing environment, where the application of audit judgment is critical, its significance becomes even more pronounced under conditions of high uncertainty and limited time. This study focuses on the factors influencing auditors’ audit judgment, particularly locus of control, self-efficacy, and time budget pressure. Audit judgment is essential when auditors are confronted with task complexity and incomplete information, requiring them to exercise professional discretion in evaluating and determining audit outcomes. This research adopts a bibliometric literature review method, wherein relevant scientific articles published in the Scopus database between 2015 and 2025 were systematically collected, screened, and analyzed using VOSviewer software. Through this bibliometric approach, the study identifies publication trends, dominant keywords, co-authorship patterns, and thematic clusters related to the factors affecting audit judgment. The review highlights key variables such as locus of control—which pertains to auditors' perceived control over their professional responsibilities; self-efficacy—which reflects their belief in their ability to carry out audit tasks effectively; and time budget pressure—which represents the constraints imposed by limited time during audit engagements. Additionally, the findings indicate that task complexity serves as a moderating variable that may amplify or diminish the effects of these factors on the quality of audit judgment.